ANALYSIS OF COMPLETE NUTRITIONAL PROFILE OF AMORPHOPHALLUS CAMPANULATUS TUBER CULTIVATED IN HOWRAH DISTRICT OF WEST BENGAL, INDIA - Basu, Subhashree; Das, Moumita; Sen, Anurupa; RoyChoudhury, Utpal; Datta, Gouriprosad (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: This work aims to analyze the proximate composition, minerals and vitamins content in the popularly consumed tuber of West Bengal, Amorphophallus campanulatus. Methods: The plant species were collected from farmers of Santragachhi, Howrah district and authenticated by Botanical Survey of India, Howrah district, West Bengal, India. Fresh tubers were analyzed for their content of crude proteins, total carbohydrate, soluble carbohydrate, fat, fibre, ash, moisture, carotenoids and vitamins. Mineral content was detected from the ash using Inductively Coupled Plasma Atomic Spectrophotometer. Results: The study reveals that the tuber of Amorphophallus campanulatus has high crude protein, moisture, fibre, ash, vitamin E and C content. Besides, the tuber is rich in almost all the essential macro and micro-nutrients. The tuber is interestingly an important source of potassium, calcium and sodium. Moreover, the tuber also lacks the presence of heavy metals like mercury, cadmium, lead and arsenic. Conclusion: Thus the results of the study form an important contribution to the knowledge about the complete nutritional profile of this tuber, which can lead to enhancement of its consumption for maintenance of healthy lifestyle and focus on its therapeutic approach as future perspective. Keywords: Amorphophallus campanulatus, Macro Micro-Nutrient, Nutritional Profile, Proximate Composition